Effect of resistance training on headache symptoms in adults: Secondary analysis of a RCT. (December 2017) - Andersen, C.H.; Jensen, R.H.; Dalager, T.; Zebis, M.K.; Sjøgaard, G.; Andersen, L.L.
Abstract: Background: While strength training for the neck and shoulder muscles may be effective in reducing headache, the optimal combination of exercise frequency and duration is unknown. This study investigates the effect of different time-wise combinations of one weekly hour of strength training for the neck and shoulder muscles on headache frequency, intensity, and use of analgesics. Methods: A total of 573 office workers were randomly allocated at the cluster-level to five groups; 3 × 20 min a week of minimally supervised (3MS), 1 × 60 (1WS), 3 × 20 (3WS) or 9 × 7 (9WS) min a week of supervised high-intensity strength training for 20 weeks, or to a reference group without training (REF). Headache frequency, intensity, and use of analgesics in relation to headache were determined by questionnaire at baseline and follow-up. Results: The intention-to-treat analysis showed reduced headache frequency and intensity of approximately 50% in all training groups compared with REF at 20-week follow-up (P < 0.001). Use of analgesics was lower in the supervised training groups (1WS, 3WS and 9WS), but not in the group with minimal training supervision (3MS), compared with REF at follow-up. Conclusion: One hour of specific strength training – regardless of the distribution during the week - effectively reduced both headache frequency and intensity in office workers. Thus, a large time-wise flexibility exists when implementing specific strength training at the workplace. However, only supervised training led to a reduction in use of analgesics for headache. Highlights: One hour weekly of strength training reduced headache frequency and intensity. There is time-wise flexibility when implementing specific strength training. Supervised training was accompanied by a reduction in use of analgesics for headache.